The effect of Brucellosis in Wildlife in four Major National Parks of Uganda - Aruho, Robert; MacLeod, Ewan T.; Manirakiza, Leonard; Rwego, Innocent B. (BMC Veterinary Research, 2021)
Brucellosis is a contagious zoonotic disease of great public health and economic significance especially in developing countries. The disease affects humans and several species of livestock and wildlife. Studies on Brucellosis in wildlife in Uganda have been limited to single populations particularly in Queen Elizabeth National Park. This study aimed at estimating the percentage of positive samples of Brucella spp. in wildlife in four major national parks of Uganda. This was a retrospective survey which utilized archived samples collected from wildlife during the annual disease surveillance activities between 2013 and 2017.A total of 241 samples from seven species namely African buffalo (Syncerus caffer, n = 109), African elephant (Loxodonta africana, n = 22), giraffe (Giraffa camelopardalis rothschildi, n = 41), Uganda kob (Kobus kob thomasi, n = 36), lion (Panthera leo, n = 6), plain zebra (Equus quagga, n = 25), and bushbuck (Tragelaphus scriptus, n = 2), were tested for antibodies using the Rose Bengal Plate Test. The overall percentage of positive samples in the four national parks was 31.1% (75/241; 95% CI: 25.6–37.2). Kidepo Valley National Park had a significantly higher percentage of positive samples of 55.9% (19/34; 95% CI: 39.5–71.1) compared to other sampled national parks (p < 0.05). Lions had significantly higher percentage of positive samples at 66.7% (4/6) than African buffalo at 48.6% (53/109, p < 0.0001). There were no antibodies for Brucella spp. detected in African elephant and bushbuck.This study shows variations in percentage of positive samples with Brucella spp. between species and across national parks and notably a high percentage with Brucella spp. in wildlife in Uganda than that recorded elsewhere in sub-Saharan region of Africa. Potential for transmission to other wildlife and spill over to livestock is high especially in national parks with high livestock-wildlife interaction.
Keywords: Infectious diseases, Zoonoses, Buffaloes, Giraffe, Zebra, Lions, Elephants